PENGALAMAN ESTETIK PADA NOVEL O KARYA EKA KURNIAWAN DALAM PERSPEKTIF POSMODERNISME - Andika Hendra Mustaqim (Wanastra: Jurnal Bahasa dan Sastra, 2016)
The purpose of the research is to explore the experience aesthethic in the novel O written by Eka Kurniwan through postmodernism perspective. The research method is content analysis because it'is a literary research. The result of this research are the writer finds the experience aesthetic elements in the novel O, such as object directness, felt freedom, detached affect, active discovery, and wholeness. Besides, the writer also explores about the marriage between postmodernism and experience aesthetics in the novel O which focus on plot and character.